Bone morphogenetic protein 4 inhibits pulmonary fibrosis by modulating cellular senescence and mitophagy in lung fibroblasts. Issue 6 (15th December 2022) - Guan, Ruijuan; Yuan, Liang; Li, Jingpei; Wang, Jian; Li, Ziying; Cai, Zhou; Guo, Hua; Fang, Yaowei; Lin, Ran; Liu, Wei; Wang, Lan; Zheng, Qiuyu; et al.
Background: Accumulation of myofibroblasts is critical to fibrogenesis in idiopathic pulmonary fibrosis (IPF). Senescence and insufficient mitophagy in fibroblasts contribute to their differentiation into myofibroblasts, thereby promoting the development of lung fibrosis. Bone morphogenetic protein 4 (BMP4), a multifunctional growth factor, is essential for the early stage of lung development; however, the role of BMP4 in modulating lung fibrosis remains unknown. Methods: The aim of this study was to evaluate the role of BMP4 in lung fibrosis using BMP4-haplodeleted mice, BMP4-overexpressed mice, primary lung fibroblasts and lung samples from patients with IPF. Results: BMP4 expression was downregulated in IPF lungs and fibroblasts compared to control individuals, negatively correlated with fibrotic genes, and BMP4 decreased with transforming growth factor (TGF)-β1 stimulation in lung fibroblasts in a time- and dose-dependent manner. In mice challenged with bleomycin, BMP4 haploinsufficiency perpetuated activation of lung myofibroblasts and caused accelerated lung function decline, severe fibrosis and mortality. BMP4 overexpression using adeno-associated virus 9 vectors showed preventative and therapeutic efficacy against lung fibrosis. In vitro, BMP4 attenuated TGF-β1-induced fibroblast-to-myofibroblast differentiation and extracellular matrix (ECM) production by reducing impaired mitophagy and cellular senescence in lung fibroblasts. Pink1 silencing by short-hairpin RNA transfection abolished the ability of BMP4 to reverse the TGF-β1-induced myofibroblast differentiation and ECM production, indicating dependence on Pink1-mediated mitophagy. Moreover, the inhibitory effect of BMP4 on fibroblast activation and differentiation was accompanied with an activation of Smad1/5/9 signalling and suppression of TGF-β1-mediated Smad2/3 signalling in vivo and in vitro . Conclusion: Strategies for enhancing BMP4 signalling may represent an effective treatment for pulmonary fibrosis. BMP4 deficiency results in cellular senescence and defective mitophagy of fibroblasts and promotes fibrosis in the lung. This study provides a proof-of-principle that BMP4 activation may offer a promising therapeutic approach for pulmonary fibrosis. https://bit.ly/3HWIKWS